Woman's Angle, 1952 (1952)
1952 1945-1960 "Woman's Angle, 1952" [EP0202], 1952 August 1952 saw the first issue of Woman's Angle, a newsletter for the Women and Girls Section of the Amalgamated Engineering Union. The Union began to admit women as members in 1943, following the influx of women into the industry during the war.